ECOLOGICAL AND PHYSIOLOGICAL CHARACTERISTICS OF THE LAKE POND (MOLLUSCA: GASTROPODA: PULMONATA: LYMNAEIDAE) DUE TO THE INFLUENCE OF CADMIUM IONS IN THE AQUEOUS MEDIUM - Pinkina, Tetiana; Solomatina, Valentyna; Svitelskyi, Mykola; Ishchuk, Oksana; Matkovska, Svitlana (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
The article presents the results of research on the influence of cadmium ions (acute concentrations – 5-0,5 mg / dm3; chronically lethal – 5.10-2-5.10-3 mg / dm3; sustained – 5.10-4-5.10-5 mg / dm3; subliminal concentrations – 5.10-6 mg / dm3 and below) on the ethological, morphological and physiological parameters of lake pond. Based on many years of research, the survival of individuals in a toxic environment has been studied, depending on the concentration of the metal ion and the duration of its exposure. As a result of the study of biological peculiarities in the set of basic toxicological indices for L. stagnalis, exposed to cadmium ions of the aqueous medium, it was established that this metal is highly toxic. The study showed that the strongest toxic effects on the metabolic processes in the body of the pond have been the solutions of chronic lethal concentrations of cadmium ions. Heavy metals present in natural waters belong to a group of trace elements, which are characterized by high physiological activity in micro and ultramicrodoses. The specific biological significance of cadmium as a trace element has not been established. However, due to its chemical properties, this metal has a cumulative effect on aquatic organisms, which can replace zinc in many vital enzymatic reactions, leading to their breakage or inhibition. Cadmium is among the very poisonous substances, it can reduce reproduction and delay the development of embryos in animals. In populations, there are mechanisms that determine their density. These include, in particular, the size and age structure and survival of individuals. In the age-old specimens, the pond lobster, as well as mollusks from the same masonry, placed in the solution of heavy metal ions, usually exhibits significant variability in growth rates, size and body weight. It is known that growth processes are quite sensitive to the slightest changes in any ecological factor, therefore the size and weight characteristics of animals placed in a poisonous environment are among the parameters that characterize the organism's response to hydro-organisms to change the quality of water. Recently, the number of studies in which the effect on hydrobionts of nown lethal concentrations is studied is growing. In this case, the main attention of researchers is aimed at studying acute poisoning hydrobionts, and for him the main criterion is the level of survival. However, there are still very few works in which the toxic effects of small concentrations of heavy metals are evaluated for their prolonged action, that is, in conditions close to those existing in contaminated natural waters. Although, knowing the ability of heavy metals to cumulation, attention should be paid to the survival of animals for the long-term exposure of the toxin, because this parameter determines the effectiveness of the reproduction of molluscs. Given that in the scientific literature there is only a discrete data on the influence of various concentrations of cadmium ions on the body of molluscs, we evaluated the influence of this toxicant on the ethological, morphological and some physiological parameters of lacustrine pond. The research is relevant in view of the fact that without this nformation one can not do without the prospect of biotesting of environmental monitoring of waters.